Secure and Energy-Efficient Disjoint Multipath Routing for WSNs - Liu, Anfeng; Zheng, Zhongming; Zhang, Chao; Chen, Zhigang; Shen, Xuemin (IEEE transactions on vehicular technology, 2012)
Recent advances in microelectromechanical system (MEMS) technology have boosted the deployment of wireless sensor networks (WSNs). Limited by the energy storage capability of sensor nodes, it is crucial to jointly consider security and energy efficiency in data collection of WSNs. The disjoint multipath routing scheme with secret sharing is widely recognized as one of the effective routing strategies to ensure the safety of information. This kind of scheme transforms each packet into several shares to enhance the security of transmission. However, in many-to-one WSNs, shares have high probability to traverse through the same link and to be intercepted by adversaries. In this paper, we formulate the secret-sharing-based multipath routing problem as an optimization problem. Our objective aims at maximizing both network security and lifetime, subject to the energy constraints. To this end, a three-phase disjoint routing scheme called the Security and Energy-efficient Disjoint Route (SEDR) is proposed. Based on the secret-sharing algorithm, the SEDR scheme dispersively and randomly delivers shares all over the network in the first two phases and then transmits these shares to the sink node. Both theoretical and simulation results demonstrate that our proposed scheme has significant improvement in network security under both scenarios of single and multiple black holes without reducing the network lifetime.